PEMBELAJARAN MENULIS DI SDN SEKECAMATAN SOLOKURO, KABUPATEN LAMONGAN - Akh . Zaini (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2014)
This study is aimed to describe the planning , execution, and the problems of learning to write in grade V SDN in Kecamatan Solokuro, Kabupaten Lamongan. This research uses descriptive qualitative method, which describes all the elements associated with the planning, implementation, and problems in learning to write. This descriptive -qualitative procedure is done by conducting the procedure consisting the phases of pre-activity, ongoing activity, analysing the data and taking conclusion. The results indicate that in planning of teaching writing in general, teachers have made lesson plans, but there are still some weaknessesas seen in elements of (1) learning objectives and indicators, (2) learning materials, (3) teaching and learning process, and (4) learning method.In teaching writing, teachers apply the method of question and answer, discussion, and assignments. The problems appear in the method of learning being used: the students do not understand the writing mechanics (capital letters, punctuation, effective sentences and how to use correct spelling). To overcome the problems, the teacher must give sample or writing work sample before conducting teaching writing process.